2003
DOI: 10.1128/iai.71.8.4684-4690.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sulfolipid Deficiency Does Not Affect the Virulence ofMycobacterium tuberculosisH37Rv in Mice and Guinea Pigs

Abstract: Lipids that are found only in the cell envelope of pathogenic mycobacteria, such as those containing multiple methyl-branched fatty acids, have long been thought to play a role in pathogenesis. Among these complex lipids, sulfolipids have been the most extensively studied over the last 50 years. The numerous biological effects exhibited by purified sulfolipids on phagocytic cells led to the idea that these molecules are probably important virulence factors facilitating the intracellular survival of Mycobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 24 publications
(25 reference statements)
3
66
1
Order By: Relevance
“…These reports coupled with recent studies show that among the reasons for the attenuation of M. tuberculosis the H37Ra strain is a single nucleotide polymorphism within the phoP gene that (a) is incapable of restoring polyketide-derived acyltrehalose synthesis in a phoP-phoR knock-out mutant of H37Rv (19) and (b) inhibits secretion of proteins that are important for virulence (18). Although these results establish a strong link between PhoP with lipid biosynthesis and virulence regulation, studies using a pks2-3/4 knockout mutant of M. tuberculosis H37Rv clearly show that not polyketide-derived acyltrehaloses but rather phthiocerol dimycocerosates, which are not regulated by PhoP, are the major contributor of virulence of the tubercle bacillus (19,43,44). However, it should be noted that proteins encoded by genes of the pks2 cluster (Rv3825c-3824c-3823c) and msl3 cluster (Rv1180-Rv1182-Rv1183) (supplemental Fig.…”
Section: Discussionmentioning
confidence: 92%
“…These reports coupled with recent studies show that among the reasons for the attenuation of M. tuberculosis the H37Ra strain is a single nucleotide polymorphism within the phoP gene that (a) is incapable of restoring polyketide-derived acyltrehalose synthesis in a phoP-phoR knock-out mutant of H37Rv (19) and (b) inhibits secretion of proteins that are important for virulence (18). Although these results establish a strong link between PhoP with lipid biosynthesis and virulence regulation, studies using a pks2-3/4 knockout mutant of M. tuberculosis H37Rv clearly show that not polyketide-derived acyltrehaloses but rather phthiocerol dimycocerosates, which are not regulated by PhoP, are the major contributor of virulence of the tubercle bacillus (19,43,44). However, it should be noted that proteins encoded by genes of the pks2 cluster (Rv3825c-3824c-3823c) and msl3 cluster (Rv1180-Rv1182-Rv1183) (supplemental Fig.…”
Section: Discussionmentioning
confidence: 92%
“…SL-1 also directly inhibits macrophage priming, which results in reduced superoxide anion (O 2 -) release, reduced phagocytosis, and reduced release of IL-1 75 , and affects neutrophil signal transduction pathways 76 . Nevertheless, the role of SL-1 in the virulence of M. tuberculosis remains questionable 77 . Kato and Goren 78 showed that SL-1 damages the mitochondrial structure in synergy with TDM, but no toxic effect was noted in mice injected intraperitoneally with SL-1 alone.…”
Section: Sulpholipid-1mentioning
confidence: 99%
“…Intriguingly, the ⌬mmpL8 mutant, which lacks SL-1 but accumulates SL 1278 , shows attenuated virulence in mice (23,24). By contrast, a ⌬pks2 mutant, which lacks both SL-1 and SL 1278 , is indistinguishable from WT M. tb in mice and guinea pigs (23,26). These observations suggest that SL 1278 , and possibly other SL-1 intermediates, modulate M. tb pathogenesis.…”
mentioning
confidence: 97%